Mangrove-Based Ecotourism Development Strategy, Bulu Cindea Village, Bungoro District, Pangkep Regency - Sathira Rahmi Khairunnisa; Nurul Istiqamah Ulil Albab; Risma Handayani (ABDISAINS, 2025)
ABSTRACT This research aims to identify the potential for mangrove ecotourism and formulate management strategies to optimize the potential for mangrove ecotourism in Bulu Cindea Village, Bungoro District, Pangkep Regency. The type of research carried out was mixed (Mixed Methods). The results of this research indicate that the mangrove ecotourism of Bulu Cindea Village has become a tourist destination. However, there are several parameters that need to be improved to maximize the potential of this area. As for the strategy, namely managing the thickness of mangroves, building environmentally friendly infrastructure, and empowering local communities, this area can be utilized optimally without damaging the ecosystem. Regular monitoring and evaluation is important to assess the success of the strategy implemented and identify potential problems early. Clear regulations and zoning are needed to maintain a balance between conservation and tourism development. Apart from that, waste management resulting from tides must be integrated with a focus on monitoring, public education and waste processing. Collaboration with various parties is very important to achieve this goal. Keywords: Potential Optimization, Mangrove Ecotourism, Development. ABSTRAK Penelitian ini bertujuan untuk mengidentifikasi potensi ekowisata mangrove serta merumuskan strategi pengelolahan untuk mengoptimalkan potensi pada ekowisata mangrove Desa Bulu Cindea, Kecamatan Bungoro, Kabupaten Pangkep. Jenis penelitian yang dilakukan adalah campuran (Mixed Methods). Hasil penelitian ini menunjukkan bahwa ekowisata mangrove Desa Bulu Cindea dijadikan destinasi wisata. Tetapi, terdapat beberapa parameter yang perlu ditingkatkan untuk memaksimalkan potensi kawasan ini. Adapun stateginya yaitu pengelolaan ketebalan mangrove, pembangunan infrastruktur ramah lingkungan, serta pemberdayaan masyarakat lokal, kawasan ini dapat dimanfaatkan secara optimal tanpa merusak ekosistemnya. Monitoring dan evaluasi yang rutin penting untuk menilai keberhasilan strategi yang diterapkan serta mengidentifikasi potensi masalah sejak dini. Regulasi dan zonasi yang jelas diperlukan untuk menjaga keseimbangan antara konservasi dan pengembangan pariwisata. Selain itu, pengelolaan sampah akibat pasang surut harus diintegrasikan dengan fokus pada pemantauan, pendidikan masyarakat, serta pengolahan sampah. Kolaborasi dengan berbagai pihak sangat penting untuk mencapai tujuan ini. Kata kunci: Optimalisasi Potensi, Ekowisata Mangrove, Pengembangan.